The Aesthetics of the Arabic Language in Expressing Human Relationships: A Rhetorical-Analytical Study Between Tradition and Contemporary Contexts - Alotaibi, Fahad Nawaf (Journal of Arabic Language Sciences and Literature, 2025)
This study aims to analyze the aesthetic expressions of the Arabic language in human relationships, focusing on love, friendship, and hospitality, through classical texts and modern digital discourse. It adopts a descriptive-analytical method and applies rhetorical analysis tools to traditional and digital samples. Findings show Arabic’s strong capacity to express emotions through rhetorical devices such as simile and metaphor, with a notable 22% increase in engagement in digital content. The study recommends enhancing rhetorical education and encouraging the use of Classical Arabic in media platforms.